Advances in Molecular Breeding Towards Salinity and Drought Tolerance [electronic resources]: - Jenks, Matthew A.; Hasegawa, Paul M.; Jain, S. Mohan; SpringerLink (Online service) (Dordrecht : Springer, 2007)
PSZJBL